Evaluation Protocol of Speech Discrimination in Noise with Auditory Implants: Protocolo de Avaliação da Discriminação da Fala no Ruído com Implantes Auditivos - Peixoto, Maria Conceição; Miranda, Cristina; Bento, Mafalda; Oliveira, Susana; Silva, Victor Correia (Gazeta Médica, 2018)
INTRODUCTION: Speech discrimination in noise as well as musical interpretation are among the greatest challenges of a patient with an auditory implant. The objective was to present speech discrimination in noisy environments tests and to evaluate their use in daily clinical practice. METHODS: The authors proposed a protocol for assessing speech discrimination in noisy environments for patients who are candidates for auditory implantation, in order to evaluate the integration of binaural information. Four loud-speakers were used, arranged in azimuth 0°, 90°, 180° and 270°. It was presented the conjugation of words/ sentences with speech noise or cafe sound in four possible conditions, being in the overall evaluated 16 parameters. RESULTS: The result is the percentage of words and sentences repeated correctly. Pre and postoperative comparison was performed. CONCLUSION: In parallel with the study of the spatial location of sound, it is considered that this evaluation will allow the understanding of the integration of hearing information in patients with auditory implants and their real binaural integration.